2011
DOI: 10.1021/ja202908z
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Complements to the Alzheimer's Disease Biomarker β-Amyloid Isoforms Aβ1–40 and Aβ1–42 for Blood Serum Analysis under Denaturing Conditions

Abstract: Treatment of Alzheimer's disease (AD) is plagued by a lack of practical and reliable methods allowing early diagnosis of the disease. We here demonstrate that robust receptors prepared by molecular imprinting successfully address current limitations of biologically derived receptors in displaying affinity for hydrophobic peptide biomarkers for AD under denaturing conditions. C-terminal epitope-imprinted polymers showing enhanced binding affinity for Aβ1-42 were first identified from a 96-polymer combinatorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 21 publications
0
48
0
2
Order By: Relevance
“…Because MIPs contain ''tailor-made'' binding sites, they have high selectivity and affinity for the template. The molecular recognition ability of MIPs allows these materials to be used in various fields such as chemical analysis and detection, 6,7 separation and purification, 8 drug delivery, 9 and catalysis. 10 …”
Section: Molecular Imprintingmentioning
confidence: 99%
“…Because MIPs contain ''tailor-made'' binding sites, they have high selectivity and affinity for the template. The molecular recognition ability of MIPs allows these materials to be used in various fields such as chemical analysis and detection, 6,7 separation and purification, 8 drug delivery, 9 and catalysis. 10 …”
Section: Molecular Imprintingmentioning
confidence: 99%
“…In a review on diagnostic strategies of Alzheimer's disease, authors concluded that epitope imprinting of key proteins are the most promising strategy for this disease. Diagnosis of Alzheimer's disease via imprinting was attempted by detecting the β amyloid peptides [32]. C-terminal epitope-imprinted polymers for Aβ142 were first identified through combinatorial library, and then it was used to synthesize MIPs for the β-amyloid isoforms under denaturing condition.…”
Section: Citationmentioning
confidence: 99%
“…These epitope imprinting approaches are applicable even in organic solvents used for traditional small-molecule imprinting, because small peptides are not subject to the major conformational and degradation problems which occur in whole-protein imprinting [33][34][35][36].…”
Section: Rational Design Of Protein-imprinted Materialsmentioning
confidence: 99%